Understanding the role of the state in the governance of security in South Africa: a Muizenberg improvement district case study - Mpala, Nokuthula (Institute of Criminology, 2026)
Changes in the governance of security have increasingly challenged the role of the state as the sole provider of security due to the increasing plurality of security providers. This change often brings about questions as to what role the state plays and how active it is in governing security. Two theories have been postulated to explain the state's role in these changing times, namely the nodal governance theory and the state anchored pluralism theory. Because certainty on the state's role depends on empirical inquiry, this paper is based on research conducted in an area with a plurality of security providers, namely, the space demarcated for the Muizenberg Improvement District. It examines the relationship between the state and the various auspices and providers within that area. Before concluding on how the Muizenberg scenario supports the nodal governance theory in that the state is a node among other nodes as opposed to an anchor, this paper examines concepts important to this paper namely 'governance' and 'security' and further examines in detail the two theories at hand.